The Broken Home Students in the Grip of Capitalism: An Analysis of Alienation and Identity Crisis Based on Erich Fromm's Theory - Moh. Syamsi Dhuha; Zengenene Maybe (Master's Program in Sociology, Faculty of Social and Political Sciences, Universitas Negeri Surabaya, 2025)
This study examines how the capitalist system in higher education creates and deepens experiences of alienation and identity crises among students from broken homes. Using Erich Fromm's theory of alienation as the main conceptual framework and the Global South approach as a structural perspective, this study was conducted using a critical qualitative approach and case study design. Data were collected through in-depth interviews with six undergraduate students from three state universities in Surabaya who come from broken homes and face financial pressures. The findings reveal that the logic of capitalism, manifested in academic competition, financial demands, and the commodification of education, reinforces feelings of alienation, powerlessness, and identity disorientation. The Global South approach highlights how these experiences are influenced by the structural position of historically and globally marginalized developing countries. However, the informants demonstrated agency by creating alternative support systems through peer relationships and forming new, more adaptive identities. Fromm's concept of alienation is reflected in the struggle to cope with emotional disconnection, loss of self, and pressure to conform to global market standards. This study concludes that capitalism reinforces structural vulnerability but also drives strategies of resistance and identity negotiation in the Global South context.